Adsorption of Flagyl on Prepared Ash from Rice Husk - Abbas, Haider; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
In recent years, it has been evident that searching for alternative methods with low-price and eco-friendly features that produce high-quality adsorbents is in high demand. In the present work, Rice husk from Iraqi rice named (Amber) had been used as the primary source to produce rice husk ash (RHA) for the removal of the antibiotic metronidazole (Flagyl) from water. After optimum drying of rice husk, rice husk ash (RHA) was obtained at 600 °C using an electric oven. RHA has been investigated for properties using X-ray diffraction (XRD), porosity, and surface area (SA). The experimental work adsorption data were optimized to evaluate Langmuir and Freundlich constants. The thermodynamic parameters likely a change in Gipp's energy (ΔG), enthalpy (ΔH), and entropy (ΔS). The impacts of increasing temperature on adsorption capacity were investigated, and the results indicate that the pseudo-second-order kinetics model could be presented the dynamic adsorption data that it has. The resultant values for the heat of adsorption and the free energy indicated that adsorption of Flagyl is preferred at low temperatures.